1987
DOI: 10.1055/s-2006-962739
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Studies in Indole Alkaloid Accumulation and Changes in Tryptophan Decarboxylase and Strictosidine Synthase Activities: A Comparison in Three Strains ofCatharanthus roseusCells

Abstract: Three different strains of CATHARANTHUS ROSEUS cells were compared during one subculture with regard to tryptophan, tryptamine, ajmalicine, serpentine contents and tryptophane decarboxylase (TDC) (4) and Strictosidine synthase activities. The strains differed greatly in their accumulation of tryptamine and alkaloid. The TDC of all three strains showed the highest activity during the growth phase and declined sharply at the end of this phase. On the contrary, strictosidine synthase activity was the lowest durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…However, ajmalicine production varied in the different cultures. Such a lack of correlation between SSS activity measured in vitro and the capacity of alkaloid accumulation by the cells was also reported by Doireau et al (1987).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, ajmalicine production varied in the different cultures. Such a lack of correlation between SSS activity measured in vitro and the capacity of alkaloid accumulation by the cells was also reported by Doireau et al (1987).…”
Section: Discussionsupporting
confidence: 55%
“…Their activities declined during the growth phase and increased continuously after reaching the stationary phase of growth (day 5). Doireau et al (1987) and Stevens et al (1992) observed the same negative relationship between growth and SSS activity in different cell lines of C. r o s e u s . In all culture conditions examined, SSS reached similar maximum activity levels.…”
Section: Discussionmentioning
confidence: 52%
“…The messenger RNA for STR presents a region that encodes for a signal peptide of 31 amino acids that directs it to the vacuole (Pasquali et al 1992), which supports diverse tests that suggesting that STR is a vacuolar enzyme (McKnight et al 1991;Stevens et al 1993). Doireau et al (1987), and Stevens et al (1992) have measured the activity of TDC and STR, as well as the concentrations of tryptamine in suspension cultures of C. roseus and other species. These authors observed a tryptamine accumulation in spite of having a high activity of STR.…”
Section: Biosynthesis Of the Tiassupporting
confidence: 57%
“…The addition of geraniol, 10-hydroxygeraniol and secologanine, precursors of the terpenic pathway, increases the alkaloid content, specially tabersonine, in cellular suspensions, which seems to suggest that the production of alkaloids can be limited by one or more steps of the terpenic pathway (Merillon et al 1986;Schiel et al 1987;Doireau et al 1987;Facchini and DiCosmo 1991;Shanks et al 1998;Morgan and Shanks 2000). This conclusion cannot be generalized since contradictory evidence exists, such as the increase in the alkaloid production by means of the tryptamine addition to the culture medium (Zenk and Deus 1982).…”
Section: Regulationmentioning
confidence: 99%
“…Ajmalicine and serpentine come from the same side branch of the main pathway leading to vindoline, catharanthine and the dimeric antineoplastic compounds, vincristine and vinblastine (Noe et al, 1984;Merillon et al, 1986;Doireau et al, 1987). Ajmalicine is converted into serpentine through the activity of vacuolar basic peroxidases (Blom et al, 1991) and this conversion seems to be light-dependent (Knobloch et al, 1982).…”
Section: Discussionmentioning
confidence: 99%